The Determinants of Common Stock Returns Volatility: An International Comparison: Discussion - Lessard, Donald R. (Journal of Finance, 1976)
Donald R. Lessard, The Determinants of Common Stock Returns Volatility: An International Comparison: Discussion, The Journal of Finance, Vol. 31, No. 2, Papers and Proceedings of the Thirty-Fourth Annual Meeting of the American Finance Association Dallas, Texas December 28-30, 1975 (May, 1976), pp. 751-752